The Effect of the Coronavirus Disease 2019 Pandemic on University Students' Mental Health and Life Quality: A Retrospective Cohort Study - Albakri, Khaled; Alabdallat, Yasmeen; Khaity, Abdulrhman; Samhouri, Jehad Feras (International Journal of Medical Students, 2023)
Background: Mental health disorders and low quality of life are considered common psychiatric problems resulting from the COVID-19 pandemic. Despite the significant importance of the knowledge and research about COVID-19 mental consequences, few studies are addressing it locally in Jordan. Therefore, the present study aims to investigate the effect of the coronavirus disease 2019 (COVID-19) pandemic on university students' mental health and life quality. Method: A retrospective cohort study was undertaken for students in Jordanian universities using an online questionnaire. Our survey consisted of the Generalized Anxiety Disorder 2‐item (GAD-2), The Patient Health Questionnaire 2-item (PHQ-2), UCLA Loneliness Scale, and the COVID-19–Impact on Quality of Life (COV19-QoL) scale to examine students' quality of life, loneliness, besides examining the difference between depression and anxiety, independently, before and during COVID-19 pandemic among Jordanian universities students. We analyzed the data using SPSS Software version 26. Results: The study included 537 participants, 371 (69.1%) of them were female, with a mean age of participants equal to 19.1 ± 0.84, with a range of 17 to 22 years. Most of the participants were second-year students 393 (54.6%) and more than half of the participants never weekly exercised. the prevalence of depression, anxiety, and loneliness after the COVID-19 pandemic were 305 (56.8%), 311 (57.9%), and 371 (69.1%); respectively. Chi-square analysis revealed that females with loneliness, depression, and anxiety were statistically predominant (p=0.014, p=0.023, p=0.000; respectively). In contrast, there was no significant difference among basic academic years students in terms of these mental outcomes. The impact of the Covid-19 pandemic on depression scores of singles was significantly higher than those who were in relationships (p= 0.008). The less depressed students were those who sleep at the night and those who have hobbies (p=0.02, p=0.007; respectively). Conclusion: Our study results highlighted and supported a significant change in the participants’ scores regarding their mental status before and after the outbreak. Furthermore, several factors preserve the mental health of students against the consequences of the COVID-19 crisis, such as gender, having hobbies, being in a relationship, bedtime, and sleep hours. Additionally, the study found that loneliness, anxiety, and depression can predict life quality. Eventually, the government should provide more attention to the student’s psychological issues. Future research should investigate which group of students have more susceptibility to being mentally affected by similar outbreaks to develop specific and efficient actions that are targeted to these certain groups, thus improving the chance of the psychological benefits.